Análisis de residuos de construcción y demolición (RCD) para su reutilización en obras de ingeniería civil (2021)
The construction generates many projects and civil works on a daily basis and, increasingly, the human being seeks through their ingenuity to design buildings, structures that allow you to live always with a better quality of life; perhaps by globalization and the continued technology boom that constantly evolves without stopping. However, this type of activities, carry in their processes, excess material (debris) called construction and demolition wastes (CDW), here is derived from a quite common and inevitable factor that refers to pollution, especially a problem of environmental and social type, when not in proper management and concerned. This research analyzed the importance and the impact of the CDW on the environment. Based on all the information gained through a bibliographic review about tests, laboratory tests and experimental processes with reference to the uses and new treatments for these materials. By analyzing their characteristics from a morphological, physical, chemical, and mineralogical noted the benefits of recycling and reusing these materials through its transformation and adding in the creation of new products for the construction of traditional and modern structures. Also, is important to mention that recourse must be had to sustainable construction to take advantage of all these materials involved, most of which can be reused and recycled. The great impact that provides the CDW needs good planning as factors such as the economic, social, and environmental, of course; the latter being the more delicate because the world in which we live, and it is global warming.